1996
DOI: 10.1007/bf00212960
|View full text |Cite
|
Sign up to set email alerts
|

Increase in aqueous humor production following D1 receptors activation by means of ibopamine

Abstract: These experimental data have a diagnostic value in glaucoma, since they show how an intraocular hypertensive response due to ibopamine in normotensive eyes is a sign of initial outflow impairment. Moreover, the possibility to increase the aqueous humor production sets new trends in the treatment of post surgical ocular hypotony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
12

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 7 publications
0
28
0
12
Order By: Relevance
“…22 Previous studies have demonstrated that ibopamine eye drops can cause an IOP increase in subjects having a reduced functioning of the outflow structures, which include patients with: POAG, normal tension glaucoma, positive family history, and hydrodynamic disorders caused by corticosteroids; healthy patients, on the other hand, tend to show no influence on IOP with ibopamine. 23,24 The ibopamine test has been reported to be an efficient provocative test in the management of glaucoma and patients at risk.…”
Section: Introductionmentioning
confidence: 99%
“…22 Previous studies have demonstrated that ibopamine eye drops can cause an IOP increase in subjects having a reduced functioning of the outflow structures, which include patients with: POAG, normal tension glaucoma, positive family history, and hydrodynamic disorders caused by corticosteroids; healthy patients, on the other hand, tend to show no influence on IOP with ibopamine. 23,24 The ibopamine test has been reported to be an efficient provocative test in the management of glaucoma and patients at risk.…”
Section: Introductionmentioning
confidence: 99%
“…A epinina combina-se com receptores alpha adrenérgicos e D1 dopaminérgicos que causam,respectivamente, após sua ativação, midríase não cicloplégica e aumento na produção de humor aquoso. Devido à deficiente drenagem intraocular presente em indivíduos glaucomatosos, estes pacientes apresentam aumento da Pio significativo quando submetidos à aplicação de ibopamina tópica (2,5,7) . Seguindo este princípio, diversos testes foram estudados como indicadores prognósticos do glaucoma, como os testes de sobrecarga hídrica, provocativos de midríase e ensaios terapêuticos (8) .…”
Section: Discussionunclassified
“…O efeito hipertensivo da ibopamina tópica é transitório (150 a 180 minutos) e não está relacionado à midríase e sim, ao aumento da produção de humor aquoso (3)(4)(5)(6) .…”
unclassified
“…(11,12) Estudos indicam que um teste provocativo, utilizando a ibopamina a 2%, pode ser muito útil na avaliação do glaucoma. (13,14) A ibopamina (3,4) (di-isobutirilester de N-metildopamina) é um análogo da epinina, que é uma catecolamina que exibe atividade tanto nos receptores adrenérgicos como dopaminérgicos. A ação adrenérgica causa uma midríase não cicloplégica, enquanto que a ação dopaminérgica leva a um aumento da produção do humor aquoso.…”
Section: Descritoresunclassified